THE SHAPE OF ASSIKO’ KANA (Hybrid Contract) ON MAKASSAR NATIVES : ETHNOMETHODOLOGY PERSPECTIVE - Syah, Sultan -; Sukoharsono, Eko Ganis; Saraswati, Erwin -; -, Roekhudin - (The International Journal of Accounting and Business Society, 2020)
ABSTRACTPurpose — The purpose of this research is to discuss the accounting shari’a in assikko’ kana (hybrid contract) applied by Makassar natives by interpreting the existence of accounting in the trade activity area.Design/methodology/approach — In order to determine the existence of accounting, this research uses a qualitative method by using the ethnomethodology approach.Findings —  The result reveals that accounting is the accountability process of economic, social, cultural, and religious aspects of the trade activities, which also can be found in the kalula[1] system. The research also finds that the trade actors are highly committed to trusting each other even though they incur losses. Thus this indicates that sociability becomes their priority. In addition, there is one more important factor so-called papalele (shareholders) whos contribute to the run of activities.Practical Implications —  Banking, financial companies, and Islamic finance including capital owners can benefit from the preparation of assikko’ kana (hybrid contracts) so that the contracts made do not conflict with the prevailing Islamic ShariaOriginality/value —  a hybrid contract form applied to the flying fish fishermen community (patorani) is the result of acculturation between local culture and Islamic law. What's interesting is that the majority of Islamic banking and financial products and services are hybrid contracts, but the source of funding is still sourced from local investors (papalele). This paper tries to make a reality in the patorani community in establishing Sharia parameters, about how to combine more than one contract in one transactionKeywords Accounting Shari’a, Hybrid Contract, PatoraniPaper Type Research paper